2013
DOI: 10.1007/s11663-013-9854-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing on Properties of Carbonaceous Materials. Part II: Porosity and Pore Geometry

Abstract: The pore structure of carbonaceous materials was studied using image analysis. The effect of annealing on the porosity and pore geometry of cokes, chars, and pyrolyzed coals (laboratory chars) was examined in the temperature range of 973 K

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…On the other hand, Echterhoff 7) conducted the Micum test of coke at 1 323 K and observed a general deterioration in the coke strength when the temperature increased above the coking temperature. This phenomenon was also confirmed by Bradshaw et al 8) Patrick et al 11) observed a degradation of tensile strength of cokes when tested at 1 723 K. Xing et al 9,10) examined the effect of annealing of cokes, chars and pyrolysed coals in the temperature range of 973 to 1 773 K on tensile strength measured at room temperature. The tensile strength of chars and pyrolysed coals was strongly enhanced by annealing in the temperature range of 973-1 373 K. The tensile strength of cokes was slightly decreased by the heat treatment after the annealing temperature increased above 1 573 K. Coke degradation upon heating to temperatures close to the raceway flame temperature was not studied.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…On the other hand, Echterhoff 7) conducted the Micum test of coke at 1 323 K and observed a general deterioration in the coke strength when the temperature increased above the coking temperature. This phenomenon was also confirmed by Bradshaw et al 8) Patrick et al 11) observed a degradation of tensile strength of cokes when tested at 1 723 K. Xing et al 9,10) examined the effect of annealing of cokes, chars and pyrolysed coals in the temperature range of 973 to 1 773 K on tensile strength measured at room temperature. The tensile strength of chars and pyrolysed coals was strongly enhanced by annealing in the temperature range of 973-1 373 K. The tensile strength of cokes was slightly decreased by the heat treatment after the annealing temperature increased above 1 573 K. Coke degradation upon heating to temperatures close to the raceway flame temperature was not studied.…”
Section: Introductionmentioning
confidence: 60%
“…[6][7][8][9][10][11] Grant et al 6) found that the compressive strength of cokes at 1 673 K was higher than that at ambient temperature. On the other hand, Echterhoff 7) conducted the Micum test of coke at 1 323 K and observed a general deterioration in the coke strength when the temperature increased above the coking temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, plots of weight change vs porosity increment for gasification and annealing are quite different, which can be attributed to the different mechanisms of porosity development. During gasification, the coke weight loss was mainly caused by the Boudouard reaction Besides the Boudouard reaction, the carbon-mineral reaction occurred below 1400 °C as well as the moisture and volatile matter release also contributed to the change of pore structure during gasification Figure presents micrographs of the bio-coke gasified to different stages.…”
Section: Resultsmentioning
confidence: 99%
“…After conversion, the pores and walls of the cokes were represented by black and white areas, respectively. The total porosity of cokes was calculated using ImageJ as the area fraction of the black area …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation